In defense of Dharma : just-war ideology in Buddhist Sri Lanka - Bartholomeusz, Tessa J. (RoutledgeCurzon critical studies in Buddhism., 2002)
"This is the first book to examine war and violence in Sri Lanka from the perspective of cross-cultural studies on just-war tradition and theory. in a study that is textual, historical, and anthropological, it is argued that the ongoing Sinhala-Tamil conflict is often justified by resorting to religious stories that allow for war when Buddhism is in peril. Since Buddhism is often commonly assumed to be a religion that never allows for war, this book - by suggesting otherwise - brings Buddhism into the ethical dialogue on religion and war. Without a realistic consideration of just-war thinking in contemporary Sri Lanka, it will remain impossible to understand the existing power of religion that can create both peace and war."--Jacket